The Impact of Google Classroom-Based Blended Learning on the Mastery of Social Studies Material and Thinking Skills of Students at SMPN 8 SATAP - Salfil, Salfil; Rahmawan, Ardi; Haryanto, Lutfin (JUPE : Jurnal Pendidikan Mandala, 2025)
The results of the study show that the implementation of Google Classroom–based blended learning had a significant effect on improving students’ mastery of subject matter and thinking skills. The average N-Gain score in the experimental class for material mastery was 0.63 (medium–high category), while the control class obtained 0.38 (medium category). In terms of thinking skills, the experimental class achieved an N-Gain of 0.65, whereas the control class reached 0.34. Qualitative analysis based on classroom observations also demonstrated consistent improvement across several aspects—activeness, collaboration, independence, enthusiasm, and digital engagement—with an average increase ranging from 85% to 90%. The application of blended learning proved to create a more flexible and interactive learning environment, fostering students’ intrinsic motivation. Students exhibited noticeable improvement in critical and reflective thinking through online discussions, collaborative tasks, and project-based assessments. Teachers acted as facilitators, monitoring students’ progress through the feedback features in Google Classroom, which enabled a more adaptive and personalized learning process. The study concludes that the Google Classroom–based blended learning model is effective in enhancing students’ achievement in Social Studies and their thinking skills at SMPN 8 SATAP. It is recommended that junior high school teachers maximize the use of digital platforms by integrating collaborative and reflective approaches into Social Studies learning. Moreover, schools and educational authorities should provide continuous professional development to strengthen teachers’ technology-based pedagogical competence.